Odpowiedź :
a)
[tex] \frac{2}{x} = \frac{1}{7} \\ 2 \times 7 = 1 \times x \\ x = 14[/tex]
b)
[tex] \frac{x + 1}{3} = \frac{2}{5} \\ (x + 1) \times 5 = 2 \times 3 \\ 5x + 5 = 6 \\ 5x = 1 \\ x = \frac{1}{5} [/tex]
c)
[tex] \frac{x - 2}{x + 4} = \frac{1}{6} \\ (x - 2) \times 6 = (x + 4) \times 1 \\ 6x - 12 = x + 4 \\ 5x = 16 \\ x = \frac{16}{5} [/tex]
d)
[tex] \frac{2x - 1}{2 - 3x} = \frac{3}{5} \\ (2x - 1) \times 5 = (2 - 3x) \times 3 \\ 10x - 5 = 6 - 9x \\ 19x = 11 \\ x = \frac{11}{19} [/tex]
e)
[tex] \frac{4}{x + 2} = \frac{5}{x} \\ 4 \times x = (x + 2) \times 5 \\ 4x = 5x + 10 \\ - x = 10 \\ x = - 10[/tex]
f)
[tex] \frac{0.3x - 1}{2} = \frac{2x - 7}{3} \\ (0.3x - 1) \times 3 = (2x - 7) \times 2 \\ 0.9x - 3 = 4x - 14 \\ - 3.1x = - 11 \\ - 31x = - 110 \\ x = \frac{110}{31} [/tex]
Myślę że pomogłem ;)